2013
DOI: 10.1371/journal.pone.0053103
|View full text |Cite
|
Sign up to set email alerts
|

Mac-1 Directly Binds to the Endothelial Protein C-Receptor: A Link between the Protein C Anticoagulant Pathway and Inflammation?

Abstract: ObjectiveThe endothelial protein C-receptor (EPCR) is an endothelial transmembrane protein that binds protein C and activated protein C (APC) with equal affinity, thereby facilitating APC formation. APC has anticoagulant, antiapoptotic and antiinflammatory properties. Soluble EPCR, released by the endothelium, may bind activated neutrophils, thereby modulating cell adhesion. EPCR is therefore considered as a possible link between the anticoagulant properties of protein C and the inflammatory response of neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…10). EPCR and ␤ integrins expressed on neutrophils are known to bind APC resulting in a reduction in migration (14,15,18), and our results now suggest a role for the receptors EPCR and Mac-1 in APC-mediated inhibition of NETosis. Based on molecular studies with endothelial cells and podocytes, APC ligates EPCR and cleaves PAR1 and PAR3 at noncanonical residues differing from the thrombin cleavage sites (19,24).…”
Section: Discussionsupporting
confidence: 65%
“…10). EPCR and ␤ integrins expressed on neutrophils are known to bind APC resulting in a reduction in migration (14,15,18), and our results now suggest a role for the receptors EPCR and Mac-1 in APC-mediated inhibition of NETosis. Based on molecular studies with endothelial cells and podocytes, APC ligates EPCR and cleaves PAR1 and PAR3 at noncanonical residues differing from the thrombin cleavage sites (19,24).…”
Section: Discussionsupporting
confidence: 65%
“…The ability of soluble (s)EPCR to bind Mac-1 on neutrophils indirectly through its association with PR3 26 suggests that EPCR may interfere with neutrophil adhesion to activated endothelium. 69 However, the ability of sEPCR and cell-associated EPCR to bind Mac1 directly 28 suggests that the role of EPCR in leukocyte adhesion may vary and would be dependent on the ratio of sEPCR vs cell surface EPCR.…”
mentioning
confidence: 99%
“…In this regard, Fink et al showed that soluble EPCR mediates monocyte adhesion by direct binding to Mac-1, an interaction which might possibly involve RAGE too [62]. Notably, and in contrast to the study of Fink et al ., the majority of recruited leukocytes in our experimental inflammation models are neutrophils [8], [40][43].…”
Section: Discussionmentioning
confidence: 86%